Coordination polymers and molecular structures among complexes of mercury(II) halides with selected 1-benzoylthioureas. (18th April 2015) - Okuniewski, Andrzej; Rosiak, Damian; Chojnacki, Jarosław; Becker, Barbara
Graphical abstract: Four new coordination polymers and two molecular complexes were obtained by the reaction of HgX2 (X = Cl, Br, I) with 1-benzoyl-3-phenylthiourea and 1-benzoyl-3-(2-methylphenyl)thiourea in methanol. Abstract: Six new 1-benzoyl-3-phenylthiourea and 1-benzoyl-3-(2-methylphenyl)thiourea complexes of mercury(II) were obtained in the reactions of the ligands with HgX2 in methanol (X = Cl, Br, I). Their structures, determined by single-crystal X-ray diffraction analysis, exhibit different stoichiometries and molecular organization. Coordination centers adopt more or less distorted tetrahedral geometry (five structures) or distorted trigonal bipyramidal geometry (one structure). In four cases 1D coordination polymers were formed and in the other two molecular compounds were found. In three cases solvent molecules (H2 O or MeOH) were found in crystal structure. Although all compounds share common intramolecular N–H⋯OC structural motif they exhibit unique hydrogen bonding pattern. Common p c 11 rod group symmetry of polymer chains (where applicable) allows simplified classification of the 3D packing as parallel stacking of trapezoidal prisms.